Religion and the rise of democracy - Maddox, Graham (Routledge, 1996)
In this original study, Maddox analyses the role of religion in the development of democracy from the tribes of ancient Israel to the present day. A truly interdisciplinary thesis drawing on political science, religious history and theology.